An evaluation of choice on instructional efficacy and individual preferences among children with autism. Issue 1 (28th October 2015) - Toussaint, Karen A.; Kodak, Tiffany; Vladescu, Jason C.
Abstract : The current study compared the differential effects of choice and no‐choice reinforcement conditions on skill acquisition. In addition, we assessed preference for choice‐making opportunities with 3 children with autism, using a modified concurrent‐chains procedure. We replicated the experiment with 2 participants. The results indicated that choice‐making opportunities increased treatment efficacy for 2 of the 3 participants, and all 3 participants demonstrated a preference for choice‐making opportunities.